ABU ALI IBN SINA'S VIEWS ON HEALTHY EATING - Safarova Nafisa Sulaymonovna; Mehrinisa Hamzabekovna Hamza qizi (Scholar Express Journals, 2023)
Abu Ali ibn Sina, commonly referred to as Avicenna, was a highly influential Persian philosopher, physician, and polymath during the Islamic Golden Age. In this article, we will explore Ibn Sina's perspective on nutrition, examining the theories he developed and the insights he provided, shedding light on the importance he attributed to proper dietary habits in promoting physical and mental well-being
Keywords: Abu Ali Ibn Sina; healthy eating; wellness